Synthesis of Novel Schiff Base and Azetidinone Derivatives and their Antibacterial Activity - Kamal Vashi; H. B. Naik (E-Journal of Chemistry)
A series of Compound 4-(2᾽-hydroxy-3᾽-chloro-5᾽-ethyl phen-1᾽-yl)-1-(4᾽-tolyl)-3-chloro-2-azetidinone 4a-j have been prepared by the reaction of 2 -hydroxy-3 -chloro-5 -ethyl-N-(p-tolyl)-chalconimines 3a-j with chloroacetyl chloride in the presence of triethylamine. The Schiff base derivatives 3a-j has been prepared by the condensation of different substituted chalone derivatives 1 with p-toluidine 2. The synthesized compounds were screened for their antibacterial activity against Staphylococcus aureus and Escherichia coli.